Impact of low-frequency high-power ultrasound on spoilage and potentially pathogenic dairy microbes - Cameron, Michelle (Stellenbosch: University of Stellenbosch, 2008)
Thesis (PhD (Food Science))--University of Stellenbosch, 2007.